Holocene climate dynamics derived from pollen record of Jiulongchi wetland in Fanjing Mountain, southwest China. (20th April 2019) - Gao, Yang; Xiong, Kangning; Quan, Mingying; Song, Bing; Peng, Haijun; Peng, Huirong; Shen, Weidan; Bao, Kunshan
Abstract: An alpine wetland core was obtained to a depth of 4.0 m from the Fanjing Mountain in southwest China. Sections of the core were dated with 14 C data obtained with high resolution mass spectrometry (AMS), and Holocene climate changes were inferred by categorizing predominant tree and fern vegetation identified from pollen and spore counts at various core depths. The temperature increased during 11.9–8.0 cal ka BP, and the warmest period was during 8.0–4.6 cal ka BP. Then, it gradually became cooler during the late Holocene. Our temperature estimates were in good agreement with the previous studies of the Holocene temperature in the Asian monsoon areas. There were two relatively wet periods of 10.7–8.0 cal ka BP and 4.6–2.6 cal ka BP. There was an asynchronous precipitation trend in the south, north and southwest China, which was probably due to the different monsoon impacts. In East Asian summer monsoon (EASM) area, the monsoon precipitation gradually transgressed northward during the early to middle Holocene and regressed southward during the late Holocene. Our results will be useful to improve the understanding of the coherent spatio-temporal patterns of climate evolution in EASM region in China. Graphical abstract: Image 1